Student’s Perception towards the Mosque’s Physical Identity in Banda Aceh - Dailami; Bakri, Maysarah; Rahmi, Marlisa (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Abstract. The emergence of various mosque designs today enriches the repertoire of Indonesian architecture. This is due to differences in the understanding of the community and precedents related to Islamic architecture. This phenomenon results in differing perceptions of the physical identity of mosques, including those in Banda Aceh. This research aims to understand the perceptions of UIN Ar-Raniry students regarding the physical identity of mosques in Banda Aceh. Data collection was carried out by distributing questionnaires to 100 respondents. The research results indicate that respondents consider domes as the identity of a mosque. However, respondents do not see the presence of minarets and the use of ornaments as the identity of mosques in Banda Aceh. Despite the small percentages, another important finding is that a small number of respondents believe that the use of domes, ornaments, and minarets is not a necessity in mosque design.